Retrieving records of a rare and threatened shark in a mosaic of marine-protected areas of southeastern Brazil - Santos, Paulo R. S. [UNESP] (2023)
In this study the authors use the Fishers ecological knowledge (FEK) from the south coast of the São Paulo State, in southeastern Brazil, to recover records of Atlantic nurse shark (Ginglymostoma cirratum), a threatened with extinction species, in a mosaic of marine-protected areas (MPAs) of the south coast of São Paulo, in southeastern Brazil, in the southernmost distribution of the species in the Southwest Atlantic Ocean. For half a century, in the study area only one male of G. cirratum was officially recorded, in 1967. Retrieving records from artisanal fishers, recreational anglers, fishing guides and spearfishers added 30 more records of G. cirratum, including 2 recent captures (February/2022 and May/2022), especially around coastal islands that are covered by MPAs. Two uncommon fishing techniques, but which provided the highest number of records for the species, were documented. These are fishing nets and small longlines adapted for fishing close to the rocks, being an apparently traditional activity of a few natives of the region. As Brazil has a long history of intense catches of threatened elasmobranchs and problems with fisheries monitoring, the consideration of the FEK in the fisheries monitoring carried out by the authorities can be useful to promote improvements in data collection, especially of rare and endangered species such as G. cirratum. The strengthening of the protection of the MPAs and the articulation of research and management institutions with native people and tourists who use these areas should also be considered.